Development of E-Module Based on Flip Book Media to Improve Students’ Speaking Skills - Makhroji Makhroji; Rahmiati Rahmiati; Chairuddin Chairuddin; Irma Dewi Isda (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This research aims to develop E-module teaching materials based on Flip Book media to improve students' speaking skills. This research method used research and development with the Plomp model consisting of three stages: preliminary analysis phase, development or manufacture of prototypes, and assessment. The research instrument used a questionnaire, while the data analysis technique was quantitative. Based on the results of the media product feasibility test validation, the value was 85.62%, while the media feasibility test percentage was 89.58%. Next, the practicality test with a percentage of 0.86%, the results of the feasibility test and practicality test showed that the flip book-based e-module product developed was in the very valid category and suitable for use without revision. Meanwhile, the results of the N-gain score test for increasing students' speaking skills each semester towards increasing speaking skills are in the medium category, so it can be concluded that using e-modules based on Flip Book media can improve students' speaking skills.